2017
DOI: 10.1186/s12909-017-0865-8
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ learning experiences in end-of-life care – a focus group study from nursing homes

Abstract: BackgroundDoctors often find dialogues about death difficult. In Norway, 45% of deaths take place in nursing homes. Newly qualified medical doctors serve as house officers in nursing homes during internship. Little is known about how nursing homes can become useful sites for learning about end-of-life care. The aim of this study was to explore newly qualified doctors’ learning experiences with end-of-life care in nursing homes, especially focusing on dialogues about death.MethodsHouse officers in nursing homes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Future not being important to patients in this study may partly be a consequence of their cognitive impairment;40,43 however it could relate to patients trusting health care professionals in making the right decisions for them, a finding also found by others 44. A main reported result of ACP was better and more trustful relationships between the patient, the next of kin, and the staff,45 thus making it easier to make difficult decisions together at a later time and may save time and resources. Furthermore, talking about past and present, and more generally about hopes, worries, and preferences for the future, may provide relevant information for future decisions on life-prolonging treatment.…”
Section: Discussionmentioning
confidence: 62%
“…Future not being important to patients in this study may partly be a consequence of their cognitive impairment;40,43 however it could relate to patients trusting health care professionals in making the right decisions for them, a finding also found by others 44. A main reported result of ACP was better and more trustful relationships between the patient, the next of kin, and the staff,45 thus making it easier to make difficult decisions together at a later time and may save time and resources. Furthermore, talking about past and present, and more generally about hopes, worries, and preferences for the future, may provide relevant information for future decisions on life-prolonging treatment.…”
Section: Discussionmentioning
confidence: 62%
“…Regarding interactions with medical team members, the residents acknowledged the importance of better communication within a medical team, including with nurses, which was one of the most impressive themes concerning which they reflected and learned. A recent study indicated that newly qualified doctors could learn about the importance of calmness and acceptance in EOL care from interdisciplinary role models in nursing homes [ 24 ]. Our study demonstrated that residents could learn these topics in the stages of experiential learning, including concrete experiences and reflective observations, even in teaching hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…Another report suggests that dialogue with dying patients would enable residents to realize how wonderful life can be, to become aware of the importance of being a human before being a doctor, and, finally, to cultivate their humanity [ 29 ]. It has also been said that physicians value discussions about such cases with colleagues to become professional and reflective practitioners [ 24 ]. Therefore, attending physicians should utilize reflective discussions with team members, including residents, to improve the learning environment, to reduce stress on the medical team, and, ultimately, to enhance the care of patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Although worldwide training on palliative care for health professionnals is often limited [35], interprofessional training (physicians and nurses) could optimize sharing expertise [36]. This is in line with the 76th World Health Assembly focusing on strengthening palliative care [37] and a recent study showed how nursing homes can become useful sites for learning about end-of-life care during internships [38]. A collective training program (undergraduate and postgraduate) for medical and nurse students would give an opportunity to learn from and about each other, which facilitate this recognition of each person's skills as well as a clarification of the individual role.…”
Section: Discussionmentioning
confidence: 77%